The phenomenon of military chaplaincy in the spiritual and worldview paradigm of modern Ukraine - Ірина Ломачинська (Cхід, 2022)
The article studies the genesis of the military chaplaincy phenomenon in Ukraine. The author analyses the critical models of military chaplaincy in different world armies. The spiritual ministry of the chaplain stands between the Church and the state, which forces them to be in a war-torn world, and at the same time to remain outside the mundane, given the inevitable contradictions between total obedience to the military and humble obedience to God. Religious education is a component of the system of combat and moral and psychological training of military personnel. It is entrusted with the main task - to maintain the troops' high spiritual, patriotic, and combat potential. The main stages of the formation of military chaplaincy in Ukraine in the context of its instantiation are presented in the study. In the national context, the institute of military chaplaincy exists due to the manifestations of the national liberation movement in terms of military threats, forming the image of the chaplain as not only a spiritual but a deeply patriotic personality. It is defined that a robust challenge in the formation of the national military chaplaincy was the war of Russia against Ukraine, which has mobilised the internal potential of active cooperation of state military and religious institutions in the legislative and regulatory framework of military chaplains. The article describes the peculiarities of attracting positive world experience of military chaplaincy. The relevance and novelty of the study are explained by the involvement of a systematic approach that makes it possible to analyse the formation of domestic military chaplaincy in the context of applying positive world experience and preserving its national specificity, focused on the ideological foundations of moral and patriotic education of military personnel. The main directions of religious organisations' activities in military structures are cult and worship, psychological and rehabilitation, ideological and patriotic, spiritual and moral, and motivational and social. It is found that the importance of the global challenges facing the Ukrainian state and its Armed Forces requires military chaplains not only to perform religious functions but, above all, to ensure the high moral qualities of service members, the formation of civic duty to protect the state, to foster the spirit of patriotism, brotherhood, and mutual respect.